Casein Kinase-2 Interacting Protein-1 Regulates Physiological Cardiac Hypertrophy via Inhibition of Histone Deacetylase 4 Phosphorylation - Zhao, Yinlong; Ling, Shukuan; Zhong, Guohui; Li, Yuheng; Li, Jianwei; Du, Ruikai; Jin, Xiaoyan; Zhao, Dingsheng; Liu, Zizhong; Kan, Guanghan; Chang, Yan-Zhong; Li, Yingxian (Frontiers in Physiology, 2021)
Different kinds of mechanical stimuli on the heart cause different myocardial phenotype. Different kinds of mechanical stimuli acting on the heart lead to different myocardial phenotypes. Physiological stress, such as exercise, leads to adaptive cardiac hypertrophy, which is characterized by a normal cardiac structure and improved cardiac function. Pathological stress, such as sustained cardiac pressure overload, causes maladaptive cardiac remodeling and, eventually, heart failure. Casein kinase-2 interacting protein-1 (CKIP-1) is an important regulator of pathological cardiac remodeling. However, the role of CKIP-1 in physiological cardiac hypertrophy is unknown. We subjected wild-type (WT) mice to a swimming exercise program for 21 days, which caused an increase in myocardial CKIP-1 protein and mRNA expression. We then subjected CKIP-1 knockout (KO) mice and myocardial-specific CKIP-1-overexpressing mice to the 21-day swimming exercise program. Histological and echocardiography analyses revealed that CKIP-1 KO mice underwent pathological cardiac remodeling after swimming, whereas the CKIP-1-overexpressing mice had a similar cardiac phenotype to the WT controls. Histone deacetylase 4 (HDAC4) is a key molecule in the signaling cascade associated with pathological hypertrophy; the phosphorylation levels of HDAC4 were markedly higher in CKIP-1 KO mouse hearts after the swimming exercise program. The phosphorylation levels of HDAC4 did not change after swimming in the hearts of CKIP-1-overexpressing or WT mice. Our results indicate that swimming, a mechanical stress that leads to physiological hypertrophy, triggers pathological cardiac remodeling in CKIP-1 KO mice. CKIP-1 is necessary for physiological cardiac hypertrophy in vivo, and for modulating the phosphorylation level of HDAC4 after physiological stress. Genetically engineering CKIP-1 expression affected heart health in response to exercise.